THE INFLUENCE OF SHOPPING LIFESTYLE, FASHION INVOLVEMENT, PROMOTION ON IMPULSE BUYING FASHION PRODUCTS ON TIKTOK - Rosi, Si; Astuti, Herni Justiana; Widhiandono, Hengky; Hidayah, Arini (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE - This study aims to analyze the effect of Shopping Lifestyle, Fashion Involvement, Promotion on Impulse Buying. The subjects of this study were students of Muhammadiyah Purwokerto University who used the TikTok application.METHODOLOGY - In this study using a sample of 105 respondents, quantitative methods were implemented in this study with a Purposive Sampling approach. Data collection in this study was collected through distributing questionnaires. Analysis using Smart-PLS 3.0 to test the relationship between variables. The stages use the outer model for model testing, with the inner model for structural model testing.FINDING - The stages use the outer model for model testing, with the inner model for structural model testing. The results obtained from this study are Shopping Lifestyle and Promotion have a significantly affects on Impulse Buying fashion products in the TikTok application. While Fashion Involvement has no significantly affects on Impulse Buying fashion products in the TikTok application.